SEE IT, LIKE IT, BUY IT! HEDONIC SHOPPING MOTIVATIONS AND IMPULSE BUYING - Merima Činjarević; Kasim Tatić; Srđan Petrić (Economic Review)
The purpose of this study is to examine the influence of six broad categories of hedonic shopping motivations (adventure, gratification, role, value, social, and idea shopping) and fashion consciousness on consumers’ impulse buying behavior. The online questionnaire was created using LimeSurvey, a webbased questionnaire generator tool. An online questionnaire was directed to a sample of 500 individuals in Bosnia and Herzegovina, using nonprobability convenience sampling method. A total of 224 participants completed the questionnaire, which corresponds to the response rate of 44.8 percent. The survey instrument used in this study was designed using scales that were already validated in the previous research. The results indicated that impulse buying behavior was significantly related to adventure, gratification, value and idea shopping motivations. Nevertheless, role shopping, social shopping and fashion consciousness were found not significantly related to impulse buying behavior. The findings of this study can help retailers to gain a useful insight into the shopping motivations that trigger impulse buying behavior. A focus on adventure, entertainment, excitement and sales may be an effective retailing strategy to stimulate impulse buying behavior. There are some of limitations in this study worthy of improvement and leads for future studies. A more random sampling method, sampling from different geographic locations and replication of this study in the context of other product categories are necessary to ensure reliable generalizability.